2019
DOI: 10.3390/polym12010032
|View full text |Cite
|
Sign up to set email alerts
|

Keratin Associations with Synthetic, Biosynthetic and Natural Polymers: An Extensive Review

Abstract: Among the biopolymers from animal sources, keratin is one the most abundant, with a major contribution from side stream products from cattle, ovine and poultry industry, offering many opportunities to produce cost-effective and sustainable advanced materials. Although many reviews have discussed the application of keratin in polymer-based biomaterials, little attention has been paid to its potential in association with other polymer matrices. Thus, herein, we present an extensive literature review summarizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 302 publications
(347 reference statements)
1
66
0
Order By: Relevance
“…Besides the sample with the highest keratin loading, a decrease in both elongation at break and tensile strength with an increased keratin loading was observed without significant changes in the stress–strain slope. Many authors reported [ 50 ] higher keratin loading (larger than 10 wt %) leading to significant deterioration of tensile properties, due to worse compatibility and disintegration into the material.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the sample with the highest keratin loading, a decrease in both elongation at break and tensile strength with an increased keratin loading was observed without significant changes in the stress–strain slope. Many authors reported [ 50 ] higher keratin loading (larger than 10 wt %) leading to significant deterioration of tensile properties, due to worse compatibility and disintegration into the material.…”
Section: Resultsmentioning
confidence: 99%
“…Hard keratin is formed from tightly packed filaments in the cysteine-rich proteins matrix, while soft keratin is composed of loosely packed filaments [ 144 , 146 ]. Keratin is considered as one of the most abundant natural polymers [ 147 ]. It is usually extracted under low pH in the presence of reducing agents to give rise to keratein, or of oxidizing, agents giving rise to keratose [ 145 , 148 ].…”
Section: Hydrogels Used In Dentin–pulp Complex Regenerationmentioning
confidence: 99%
“…Specifically, the chemical composition of these CFs presents cysteine (7.8 mol %), glycine (13.7 mol %), proline (9.8 mol %), serine (14.1 mol %), hydrophobic residues, and β-pleated sheets [ 2 , 3 , 4 , 7 ]. The type of keratin found in CFs (β-keratin) [ 22 , 23 , 24 , 25 ] exhibits a pleated sheet structure, as shown in Figure 1 , consisting of β-strands connected laterally (either parallel or non-parallel) through hydrogen intermolecular bonds (see the red circle in Figure 1 ) [ 22 ]. This pleated sheet structure is stable due to two main factors: (i) The hydrogen bond between β-strands allows the generation of a sheet and (ii) the planar peptide bond induces a folded sheet [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These BPFs have been morphologically, physically, and chemically characterized in several studies, whose results have highlighted their very low density (approximately 0.8 g/cm 3 ) and good thermal and sound-damping performance, among other properties [ 9 , 26 ]. In addition, these BPFs have been studied as fiber-reinforcement for generic composite materials (e.g., [ 6 , 8 , 19 , 24 , 27 , 28 , 29 , 30 ]) and also as fiber-reinforcement for cement-based and plastic-based construction composite materials (e.g., [ 7 , 11 , 19 , 22 , 27 , 28 ]). Nevertheless, the use of these BPFs as fiber-reinforcement for non-synthetic construction materials has been included in very few studies, which have mainly been focused on the use of BPFs as reinforcement in soil remediation applications [ 13 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%